Standardization of CAD Drawing Formats and GeoJSON-Based Processing for 3D Spatial Data Extraction of Underground Utilities - Jongseo Lee; Yudoo Kim; Il-Young Moon (Buildings)
The traditional construction industry has predominantly relied on labor-intensive methods, resulting in significantly lower efficiency and productivity compared to other industries. According to a report by the Korea Productivity Center (KPC), the productivity of the construction industry is approximately 24.5% lower than that of the manufacturing sector and 15.7% lower than that of the service sector, highlighting a significant productivity gap. To enhance efficiency and productivity in the construction sector, the South Korean government, led by the Ministry of Land, Infrastructure, and Transport, has announced a policy aimed at achieving 100% adoption of smart construction technologies by 2025. In this paper, we propose a methodology for standardizing the format of underground utilities plan drawings by incorporating 3D coordinates, shapes, and attribute information to facilitate the digital transformation of construction site data. Furthermore, we introduce a standardized approach for extracting data from these drawings and converting them into 3D spatial data in the GeoJSON (Geographic JavaScript Object Notation) format. The experimental results of the technology for processing structured drawings into 3D spatial data demonstrated that all data were successfully converted without any omissions.